An exceedance score for the assessment of the impact of nitrogen deposition on habitats in the UK - Woodward,H; Oxley,T; Rowe,EC; Dore,AJ; ApSimon,H (Environmental Modelling and Software, 2022)
Large areas of nitrogen-sensitive habitats are currently estimated to be in exceedance of their critical loads (CLs) as indicators for protection from nitrogen deposition. In the UK, deposition estimates from the semi-empirical Concentration Based Estimated Deposition (CBED) model are used for official reporting of current exceedances. The UK Integrated Assessment Model (UKIAM) framework is designed to provide future projections of concentrations and deposition due to projected changes in emissions. UKIAM has been extended to provide alternative deposition estimates aligned with those of CBED, and the results combined with the range in habitat CL values to create an exceedance score, leading to a probabilistic evaluation of CL exceedances. The utility of the method is demonstrated by analysing a series of hypothetical scenarios. It is shown that NH3 mitigation is likely to be four times more effective in reducing CL exceedances in the UK than the mitigation of NOx emissions.